STRATEGI MANAJEMEN FUNDRAISING WAKAF OLEH LEMBAGA WAKAF AL-AZHAR DALAM OPTIMALISASI WAKAF UANG - Agita, Ghea; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2021)
Waqf management is the process of an organization in planning, organizing, leadership, and supervising various efforts of Nazhir to support the organization in achieving optimal goals. The purpose of this study is to determine how the implementation of the cash waqf fundraising strategy implemented in the Al-Azhar Waqf institution. This research uses a descriptive qualitative approach and uses purposive sampling. The results of this study concluded that the money waqf fundraising strategy by the Al-Azhar Waqf institution was implemented using the 5 ways method of funding and increasing your waqf fund. In addition, the Al-Azhar Waqf institution in carrying out the fundraising management strategy has implemented the fundraising management functions properly, namely planning, organizing, leadership, and supervision. However, in the implementation of fundraising activities there are obstacles that need to be considered in order to launch waqf fundraising activities, namely the lack of human resources both in terms of quality and quantity. Thus, this obstacle becomes an obstacle in the productivity of fundraiser activities in optimizing the collection of waqf funds.